2016 49th Hawaii International Conference on System Sciences (HICSS) 2016
DOI: 10.1109/hicss.2016.83
|View full text |Cite
|
Sign up to set email alerts
|

How to Design Interfaces for Product Recommendation Agents to Influence the Purchase of Environmentally-Friendly Products

Abstract: This study focuses on how to design the interfaces of a product recommendation agent (PRA) that would influence its users to purchase products that are beneficial for the environment. In particular, we discuss how to design various affect cues in a PRA interface to change customers' preference levels on key environmentally related product attributes, and thus influence their final product choice. Based on the theory of affect heuristics and the General Evaluability Theory, we design three types of affective cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In situations where users do not have information about an algorithm's performance, they tend to rely on and follow the agent's recommendations (Dietvorst et al , 2015). Recent studies have shown that such systems can be designed to be persuasive or deceptive, which can lead decision-makers to make undesirable choices (Xiao and Benbasat, 2011, 2015; Yu et al , 2016). The autonomy of technology-based agents may imply that the technology makes choices with goals “in mind” that differ from those of its users.…”
Section: The Panelists' Statements: Affective and Cognitive Implicationsmentioning
confidence: 99%
“…In situations where users do not have information about an algorithm's performance, they tend to rely on and follow the agent's recommendations (Dietvorst et al , 2015). Recent studies have shown that such systems can be designed to be persuasive or deceptive, which can lead decision-makers to make undesirable choices (Xiao and Benbasat, 2011, 2015; Yu et al , 2016). The autonomy of technology-based agents may imply that the technology makes choices with goals “in mind” that differ from those of its users.…”
Section: The Panelists' Statements: Affective and Cognitive Implicationsmentioning
confidence: 99%
“…Consequently, our way of thinking and doing actions has been influenced by the digital products around us. Internet services, mobile devices, desktop computers and video games are recognised as interactive computer technology that focuses on persuasive technology research (Yu, 2012). Persuasive technology is an extremely active multidisciplinary research field focusing on the development, design and evaluation of collaborative technologies aimed at changing the awareness and actions of endusers and social influences without any kind of coercion or deception (Bawazir, Mahmud, & Abdul Molok, 2019).…”
Section: Persuasive Technology -Fogg Behaviour Model (Fbm)mentioning
confidence: 99%